2000
DOI: 10.4049/jimmunol.164.7.3902
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Specific CD4+ T Lymphocytes from Cancer Patients Are Required for Optimal Induction of Cytotoxic T Cells Against the Autologous Tumor

Abstract: This study focuses on the specific CD4+ T cell requirement for optimal induction of cytotoxicity against MHC class II negative autologous tumors (AuTu) collected from patients with various types of cancer at advanced stages. CD4+ T cells were induced in cultures of cancer patients’ malignant effusion-associated mononuclear cells with irradiated AuTu (mixed lymphocyte tumor cultures (MLTC)) in the presence of recombinant IL-2 and recombinant IL-7. Tumor-specific CD4+ T cells did not directly recognize the AuTu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
94
1
6

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(109 citation statements)
references
References 50 publications
(39 reference statements)
7
94
1
6
Order By: Relevance
“…27,28 Despite technical difficulties, the availability of CD4 + T lymphocytes is of importance because CD4 + T lymphocytes play critical roles in the generation of antigen-specific T-cell responses and in the induction of memory, providing sustained immunity. [13][14][15][16][17][18] Recently, we and others successfully grafted primary human T lymphocytes with MHC class I-restricted specificity through introduction of full-length TCR ab, chimeric single-chain and two-chain TCR genes. Introduction of these (chimeric) TCR conferred the T lymphocytes with a new MHC-restricted tumor specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Despite technical difficulties, the availability of CD4 + T lymphocytes is of importance because CD4 + T lymphocytes play critical roles in the generation of antigen-specific T-cell responses and in the induction of memory, providing sustained immunity. [13][14][15][16][17][18] Recently, we and others successfully grafted primary human T lymphocytes with MHC class I-restricted specificity through introduction of full-length TCR ab, chimeric single-chain and two-chain TCR genes. Introduction of these (chimeric) TCR conferred the T lymphocytes with a new MHC-restricted tumor specificity.…”
Section: Discussionmentioning
confidence: 99%
“…12 Additionally, the induction of tumorspecific CTL against autologous MHC class II-negative effusion-associated mononuclear cell tumors was shown to be severely impaired, indicating that CD4 + T lymphocytes are essential for the induction of protective antitumor CD8 + CTL. 16 Adoptive transfer of CD4 + tumor-specific T lymphocytes may therefore be clinically relevant for effective antitumor responses. Indeed, in mice, the adoptive transfer of activated MHC class IIrestricted, tumor-specific CD4 + T lymphocytes has resulted in de novo generation of tumor-specific CD8 + T lymphocytes and effective antitumor responses.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] Thus, when gene-modified DC expressing tumor specific antigens are to be applied in immunotumor therapy in man, it appears to be of pivotal importance that transduced antigens are also presented via the MHC class II antigen processing pathway in order to provide T cell help. 21 Specific modification of the antigen coding cDNA is a particularly attractive strategy to introduce CD4 T cell epitopes into the MHC class II processing pathway. We employed two membrane proteins, TfR and Ii that contain sorting sequences for transport to endocytic vesicles, for delivery of antigenic sequences to MHC class II processing compartments.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Additionally, clinical studies have shown that also in humans CD4 T cell help is required for optimal induction of cytotoxic T cell responses against autologous tumor cells. 21 This is probably due to the fact that many tumorspecific and tumor-associated antigens are weak antigens. 22,23 Therefore we addressed the question of whether Ad/PEI/DNA transduced DC can be exploited to generate antigen-specific MHC class II T cell responses in addition to MHC class I responses.…”
Section: Introductionmentioning
confidence: 99%
“…The generation of ␤-gal-specific CTL by protein-loaded DC has been described before (10). Yet, it also has been demonstrated that induction of a protective response requires CD4 ϩ and CD8 ϩ cells (62) and, importantly, that activation of CD8 ϩ CTL by DC priming requires CD4 ϩ cells (63). These CTL apparently were not of the memory type, because after the transfer of CD8 ϩ cells into SCID mice hardly any cytotoxic activity was recovered in TIL.…”
Section: Discussionmentioning
confidence: 99%